A lever hypothesis for Synaptotagmin-1 action in neurotransmitter release - Klaudia Jaczynska; Victoria Esser; Junjie Xu; Levent Sari; Milo M. Lin; Christian Rosenmund; Josep Rizo (Proceedings of the National Academy of Sciences, 2025)
Neurotransmitter release is triggered in microseconds by Ca 2+ -binding to the Synaptotagmin-1 C 2 -domains and by SNARE complexes that form four-helix bundles between synaptic vesicles and plasma membranes, but the coupling mechanism between Ca 2+ -sensing and membrane fusion is unknown. Release requires extension of SNARE helices into juxtamembrane linkers that precede transmembrane regions (linker zippering) and binding of the Synaptotagmin-1 C 2 B domain to SNARE complexes through a “primary interface” comprising two regions (I and II). The Synaptotagmin-1 Ca 2+ -binding loops were believed to accelerate membrane fusion by inducing membrane curvature, perturbing lipid bilayers, or helping bridge the membranes, but SNARE complex binding through the primary interface orients the Ca 2+ -binding loops away from the fusion site, hindering these putative activities. To clarify this paradox, we have used NMR and fluorescence spectroscopy. NMR experiments reveal that binding of C 2 B domain arginines to SNARE acidic residues at region II remains after disruption of region I, and that a mutation that impairs spontaneous and Ca 2+ -triggered neurotransmitter release enhances binding through region I. Moreover, fluorescence assays show that Ca 2+ does not induce dissociation of Synaptotagmin-1 from membrane-anchored SNARE complex but causes reorientation of the C 2 B domain. Based on these results and electrophysiological data described by Toulme et al. ( https://doi.org/10.1073/pnas.2409636121 ), we propose that upon Ca 2+ binding the Synaptotagmin-1 C 2 B domain reorients on the membrane and dissociates from the SNAREs at region I but not region II, acting remotely as a lever that pulls the SNARE complex and facilitates linker zippering or other SNARE structural changes required for fast membrane fusion.